Front cover: Exploring the association of dairy product intake with the fatty acids C15:0 and C17:0 measured from dried blood spots in a multipopulation cohort: Findings from the Food4Me study. Issue 4 (April 2016) - Albani, Viviana; Celis‐Morales, Carlos; Marsaux, Cyril F. M.; Forster, Hannah; O'Donovan, Clare B.; Woolhead, Clara; Macready, Anna L.; Fallaize, Rosalind; Navas‐Carretero, Santiago; San‐Cristobal, Rodrigo; Kolossa, Silvia; Mavrogianni, Christina; et al.
Abstract : Mol. Nutr. Food Res . 2016, 60, 834–845. DOI:10.1002/mnfr.201500483 The use of dried blood spot measurements for the determination of dairy consumption is investigated. The study explores the association between C15:0 and C17:0 levels in dried‐blood spots and the intake of dairy, including high‐fat and low‐fat dairy products. The results indicate that C15:0 can be used as a biomarker of high‐fat dairy intake and of specific high‐fat dairy products.